2014
DOI: 10.1371/journal.pone.0098550
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Cost of Scaling up Midwifery and Obstetrics in 58 Low- and Middle-Income Countries

Abstract: Background and MethodsTo guide achievement of the Millennium Development Goals, we used the Lives Saved Tool to provide a novel simulation of potential maternal, fetal, and newborn lives and costs saved by scaling up midwifery and obstetrics services, including family planning, in 58 low- and middle-income countries. Typical midwifery and obstetrics interventions were scaled to either 60% of the national population (modest coverage) or 99% (universal coverage).FindingsUnder even a modest scale-up, midwifery se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Fauveau et al (1991) studied a similar midwife program in Bangladesh and found that many home births were still not attended by midwives. Given the dearth of empirical evidence, researchers have attempted to use projection models to estimate the effects of scale-up (Homer et al 2014;Bartlett et al 2014). The results of this evaluation underline the need for caution in generalizing from these estimates.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…Fauveau et al (1991) studied a similar midwife program in Bangladesh and found that many home births were still not attended by midwives. Given the dearth of empirical evidence, researchers have attempted to use projection models to estimate the effects of scale-up (Homer et al 2014;Bartlett et al 2014). The results of this evaluation underline the need for caution in generalizing from these estimates.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 99%
“…3,16 These results suggest that midwifery alone can be an efficient and cost-effective option for achieving large reductions in mortality rates. 3 A specific midwifery competency, breastfeeding counseling, is the main reason that midwives have achieved greater reductions in neonatal deaths than obstetricians. 16,17 The majority (86%) of newborns delivered by midwives were exclusively breastfed by 6 weeks of age.…”
Section: Introductionmentioning
confidence: 92%
“…2 Additionally, healthcare costs will most likely decline due to a reduction of obstetric procedures and interventions. 3 Based on a report released by the Centers for Disease Control, out-of-hospital births have increased by 89% between 2004 and 2012. Of the entire US population, 66% of out-of-hospital births occurred at home, 29% occurred at a freestanding birthing center, and 5% occurred at other locations, such as physician offices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations